Preparation method of self-supporting carbon nanofiber loaded high-spinning iron monatomic catalyst and application of catalyst in flexible zinc air battery
Self-supported carbon nanofiber-loaded high-spin Fe single-atom catalysts were prepared through electrospinning technology and high-temperature pyrolysis strategies, which solved the problems of traditional catalysts not being firmly attached and low conductivity in zinc-air batteries, and achieved efficient oxygen reduction reactions and excellent zinc-air battery performance.
Patent Information
- Application Number
- CN202411679232.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional oxygen reduction catalysts have problems in zinc-air batteries, such as poor adhesion, low conductivity, easy catalyst agglomeration and easy degradation of binders, resulting in poor battery performance and short service life.
The self-supported high-spin Fe single-atom catalyst (Fe-N4/NGC-C) is prepared by electrospinning technology and high-temperature pyrolysis strategy. This catalyst achieves uniform distribution of metal Fe single atoms through the support of carbon nanofibers, improving atomic utilization and conductivity.
It achieves low load and high catalytic performance, which is better than commercial Pt/C and low spin Fe-N4-C catalysts, improves the peak power density and charge and discharge stability of zinc air batteries, and is suitable for wearable electronic devices.
Smart Images

Figure CN119581575A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible zinc-air battery materials, and specifically relates to a preparation method of a self-supporting carbon nanofiber-loaded high-spin iron single-atom catalyst and an application thereof in a flexible zinc-air battery. Background Art
[0002] The development of clean and efficient electrochemical energy and conversion devices is crucial to accelerating energy transformation and achieving carbon reduction targets. Among the current energy conversion devices, zinc-air batteries have attracted much attention due to their high theoretical energy density, eco-friendly, high safety, abundant raw materials, and low price. However, the multi-electron-proton coupled electrochemical process involved in zinc-air batteries leads to slow kinetics of oxygen reduction reaction on the air cathode, and catalysts need to be designed to accelerate the reaction process.
[0003] At present, traditional oxygen reduction catalysts exist in the form of powders. The use of powder catalysts requires binders, conductive additives and current collectors. The addition of these materials will bring the following problems: (1) The steps to successfully attach the catalyst to the air cathode are cumbersome, and the electrode preparation cost is high; (2) The use of binders will reduce the conductivity of the electrode; (3) The catalyst is prone to agglomeration and the active sites are covered, inhibiting the diffusion of ions / electrons during the ORR reaction; (4) When the electrode is exposed to a strong alkaline solution with a high oxidation potential for a long time, the polymer binder is easily degraded, causing the catalyst to fall off and shortening the battery life. Therefore, getting rid of the interference of other additives will optimize the performance of energy storage devices to a certain extent.
[0004] Carbon-based catalysts based on the planar symmetric Fe-N4-C structure are widely used in oxygen reduction reactions. However, the strong electronegativity of the symmetrically distributed N atoms is not conducive to the electron filling of the antibonding orbitals of the Fe sites. The Fe in Fe-N4-C is usually in a low spin state (LS, t 2g 5egO), which has a strong adsorption effect on oxygen intermediates, thus hindering the oxygen reduction reaction. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0006] The first aspect of the present invention provides a method for preparing a self-supporting carbon nanofiber-supported high-spin iron single-atom catalyst, comprising the following steps:
[0007] Step 1: preparing Fe-ZIF-8 powder: mixing a zinc source solution and an iron source solution to obtain a Fe-ZIF-8 precursor solution; the iron source is ferric nitrate nonahydrate; the zinc source is zinc nitrate hexahydrate;
[0008] Step 2: preparing Fe-ZIF-8 seed crystals: heating and stirring the Fe-ZIF-8 precursor solution obtained in step 1, centrifuging, washing, and drying to obtain Fe-ZIF-8 seed crystals;
[0009] Step 3: Preparation of Fe-N4 / N GC -C catalyst precursor: polyacrylonitrile and the Fe-ZIF-8 seed crystals are added to N,N-dimethylformamide solvent and stirred for 12 hours to obtain a polymer solution containing Fe; the polymer solution is treated by electrospinning technology, and under the action of a high voltage electric field, the solution is stretched and solidified to obtain Fe-N4 / N GC -C catalyst precursor;
[0010] Step 4: Preparation of Fe-N4 / N GC -C catalyst: The catalyst precursor obtained in step 3 was pre-oxidized, and the pre-oxidized sample was sintered at high temperature in a nitrogen atmosphere to obtain a self-supporting Fe-N4 / N GC -C catalyst.
[0011] As a preferred embodiment of the method for preparing the self-supporting carbon nanofiber-supported high-spin iron single-atom catalyst of the present invention: in step 1, the mass ratio of ferric nitrate nonahydrate to zinc nitrate hexahydrate is 1:28.
[0012] As a preferred scheme for the preparation method of the self-supporting carbon nanofiber-loaded high-spin iron single-atom catalyst described in the present invention: in step 2, the stirring temperature is 60°C and the time is 12 hours; deionized water is used for washing 3 to 4 times; the temperature of the vacuum oven is set to 80°C and the time is 12 hours.
[0013] As a preferred scheme for the preparation method of the self-supporting carbon nanofiber-loaded high-spin iron single-atom catalyst described in the present invention: in step 3, the mass ratio of polyacrylonitrile, Fe-ZIF-8 seeds and N,N-dimethylformamide solvent is 4:1:7.
[0014] As a preferred scheme for the preparation method of the self-supporting carbon nanofiber-loaded Fe single-atom catalyst described in the present invention: in step 3, the conditions for electrospinning are: the amount of spinning solution is 5 mL; the applied voltage is 20 kV; the propulsion speed is 1 mL / h; the receiving distance is 15 cm; and the humidity is 40-50%.
[0015] As a preferred scheme for the preparation method of the self-supporting carbon nanofiber-loaded Fe single-atom catalyst described in the present invention: in step 4, the pre-oxidation temperature is 280°C, the heating rate is 5°C / min, the sintering time is 2h, and the temperature is naturally lowered.
[0016] As a preferred scheme for the preparation method of the self-supporting carbon nanofiber-loaded Fe single-atom catalyst described in the present invention: in step 4, the high-temperature sintering temperature is 1000°C, the heating rate is 5°C / min, the sintering time is 2h, and the temperature is naturally lowered.
[0017] The second aspect of the present invention provides the use of the self-supporting carbon nanofiber-loaded high-spin Fe single-atom catalyst prepared by the preparation method in catalyzing electrochemical reactions.
[0018] Furthermore, the electrochemical reaction is an oxygen reduction reaction.
[0019] The third aspect of the present invention provides a flexible zinc-air battery, characterized in that it comprises a zinc sheet electrode, an integrated air electrode and a solid electrolyte;
[0020] The integrated air electrode is only a self-supporting Fe-N4 / N GC -C catalyst material, no additional current collector is required.
[0021] Beneficial effects of the present invention: The preparation method provided by the present invention uses electrospinning technology combined with high-temperature pyrolysis strategy to prepare self-supporting carbon nanofiber-loaded high-spin Fe single-atom catalyst (Fe-N4 / N GC -C), carbon nanofibers have the advantages of high aspect ratio, large specific surface area, strong stability, etc., can achieve uniform distribution of metal Fe single atoms, and inhibit the aggregation of electrocatalytic active sites during carbonization. This preparation method can improve atomic utilization and conductivity, and achieve low load and high catalytic performance.
[0022] The present invention provides a self-supporting carbon nanofiber-supported high-spin Fe single-atom catalyst, wherein the unpaired electrons in the 3d orbit of the Fe site can interact with oxygen species through spin-orbit coupling to weaken the reaction energy barrier. In addition, the excellent conductivity of the carbon nanofiber substrate accelerates the transfer of charge. The self-supporting carbon nanofiber-supported high-spin Fe single-atom catalyst exhibits catalytic activity superior to that of commercial Pt / C and low-spin Fe-N4-C catalysts, and the ORR half-wave potential is 0.87V.
[0023] The self-supporting carbon nanofibers loaded with high-spin Fe single-atom catalysts provided by the present invention are directly used as integrated air electrodes to assemble flexible zinc-air batteries, which not only simplifies the assembly steps and reduces the cost of electrode preparation, but also shows feasibility in practical applications. The peak power density is 136 mW / cm 2 , two flexible zinc-air batteries connected in series can drive an electronic watch with a rated voltage of 1.5V. At the same time, they exhibit excellent charge and discharge stability at different bending angles, which makes it possible for flexible zinc-air batteries to be widely used in wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0025] Figure 1 This is a physical picture of the cathode electrode material of the flexible zinc-air battery used in the sample of Example 1;
[0026] Figure 2 This is a scanning electron micrograph of the sample of Example 1;
[0027] Figure 3 This is a high-angle annular dark-field scanning transmission electron microscopy image of the sample in Example 1 corrected for spherical aberration;
[0028] Figure 4 The magnetic susceptibility curve of the sample in Example 1 varies with temperature;
[0029] Figure 5 The magnetic susceptibility curve of the sample in Example 3 varies with temperature;
[0030] Figure 6 LSV test curves of Examples 1 to 3 and comparative samples;
[0031] Figure 7 This is a physical picture of the electronic watch driven by a flexible zinc-air battery assembled with the sample of Example 1 as an integrated air electrode material;
[0032] Figure 8 The discharge curve and power density curve of the flexible zinc-air battery assembled with the samples of Example 1 and the comparative example as the integrated air electrode materials;
[0033] Fig. 9 The constant current charge and discharge curves of the flexible zinc-air battery assembled with the sample of Example 1 as the integrated air electrode material at different bending angles;
[0034] Fig.10 The Fe-N4 / N obtained in Example 1 GC Fiber particle size distribution of -C catalyst. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0036] Embodiment 1:
[0037] This embodiment provides a carbon nanofiber-supported high-spin Fe single-atom catalyst (Fe-N4 / N GC -C), the preparation method is as follows:
[0038] (1) 1.97 g of dimethylimidazole was added to 150 mL of methanol and stirred for 30 min to obtain solution A; 1.68 g of zinc nitrate hexahydrate was added to 150 mL of methanol and stirred for 30 min, and then 60 mg of ferric nitrate nonahydrate was added and stirred for another 30 min to obtain solution B; solution A was added to solution B and stirred at 60 ° C for 12 h to fully react, then centrifuged and washed three times with deionized water, and vacuum dried at 60 ° C for 12 h to obtain ZIF-8 seed crystals.
[0039] (2) 2.8g polyacrylonitrile and 0.7g ZIF-8 seed crystals were added to 4.9g N, N-dimethylformamide solvent and stirred for 12h to obtain a polymer solution containing Fe. The polymer solution was then treated by electrospinning technology. The applied electric field was 20kV, the distance between the needle tip and the roller receiver was 15cm, the propulsion speed was 1mL / h, the ambient humidity was 40-50%, the spinning solution volume was 5mL, and the solution was stretched and solidified to obtain a catalyst precursor. The catalyst was pre-oxidized by heating it to 280°C at 1°C / min in an air atmosphere and keeping the temperature constant for 2h. After natural cooling, it was carbonized in a nitrogen atmosphere and heated to 1000°C at 5°C / min and kept for 2h. After natural cooling, Fe-N4 / N GC -C catalyst.
[0040] The carbon nanofibers obtained in Example 1 supported high-spin Fe single-atom catalyst (Fe-N4 / N GC -C) The actual picture is as follows Figure 1 As shown, it exhibits a self-supporting structure and good flexibility. Fig.10 The Fe-N4 / N obtained in Example 1 GC -C catalyst fiber particle size distribution diagram, from Fig.10 It can be seen that the average fiber particle size is 460nm and the catalyst thickness is about 42μm.
[0041] Embodiment 2:
[0042] This embodiment provides a carbon nanofiber catalyst (CNFs), and the preparation method is as follows:
[0043] The preparation method is basically the same as that of Example 1, except that no ferric nitrate nonahydrate is added to solution B.
[0044] Embodiment 3:
[0045] This embodiment provides a carbon nanofiber-supported low-spin Fe single-atom catalyst (Fe-N4-C), the preparation method of which is as follows:
[0046] The preparation method is basically the same as that in Example 1, except that the carbonization treatment temperature is 800°C.
[0047] Comparative Example:
[0048] This comparative example provides a Pt / C catalyst, which is a commercial oxygen reduction reaction catalyst.
[0049] Characterization Example 1:
[0050] The morphology of the carbon nanofiber-supported high-spin Fe single-atom catalyst obtained in Example 1 was observed under a scanning electron microscope. Figure 2 shown.
[0051] from Figure 2 It can be seen that Example 1 successfully synthesized a catalyst having a tightly arranged carbon nanofiber with rough surface interwoven into an interconnected network structure.
[0052] Characterization Example 2:
[0053] The carbon nanofiber-supported high-spin Fe single-atom catalyst obtained in Example 1 was subjected to a high-angle annular dark-field scanning transmission electron microscope with spherical aberration correction. The results are as follows: Figure 3 shown.
[0054] from Figure 3 It can be seen that the isolated bright spots marked with circles are Fe atoms with different contrast from C and N.
[0055] Characterization Example 3:
[0056] The carbon nanofibers obtained in Example 1 were loaded with high-spin Fe single-atom catalysts (Fe-N4 / N GC -C) Make a curve of magnetic susceptibility versus temperature, such as Figure 4 shown.
[0057] from Figure 4 It can be seen that Fe-N4 / N GC The Fe in -C exists mainly in a high-spin state.
[0058] Characterization Example 4:
[0059] The magnetic susceptibility curve of the carbon nanofiber catalyst (Fe-N4-C) loaded with low-spin Fe single-atom catalyst obtained in Example 3 is plotted as a function of temperature. Figure 5 shown.
[0060] from Figure 5 It can be seen that the Fe in Fe-N4-C mainly exists in the low-spin state.
[0061] Characterization Example 5:
[0062] The carbon nanofiber-supported high-spin Fe single-atom catalyst (Fe-N4 / N GC-C) the average particle size of the fibers, such as Fig.10 shown.
[0063] from Fig.10 It can be concluded that Fe-N4 / N GC The average particle size of the fibers in -C is 460nm.
[0064] Test Example 1:
[0065] The electrochemical performance of the catalysts of Examples 1-3 and the comparative example was tested.
[0066] The specific process is as follows:
[0067] Catalyst ink preparation: 2 mg of catalyst, 800 μL of ethanol, and 5 μL of Nafion (perfluorosulfonic acid) were placed in a centrifuge tube and ultrasonicated for more than 30 minutes.
[0068] During the ORR test, 30 μL of catalyst ink was dripped onto the rotating disk electrode as the working electrode three times, and the catalyst loading was 0.3 mg / cm 2 The calomel electrode was used as the reference electrode and the platinum wire as the counter electrode in an oxygen-saturated 0.1M KOH solution. The tests were all performed on a CHI 660E electrochemical workstation. The voltage range of the LSV test was -0.9 to 0.05V, the scan rate was 5mV / s, and the rotation speed of the rotating disk electrode was 1600rpm.
[0069] The data obtained is as follows Figure 6 As shown, the catalyst of Example 1 exhibits an optimal ORR half-wave potential of 0.87 V, which is better than the commercial Pt / C catalyst and low-spin Fe-N4-C catalyst.
[0070] Test Example 2:
[0071] The polished zinc sheet was used as the anode, the solid electrolyte, and the self-supporting catalyst obtained in Example 1 was directly used as the self-supporting integrated air cathode to assemble a flexible zinc-air battery. Figure 7 As shown in the figure, the test was carried out on a CHI 1140E electrochemical workstation. The voltage range of the discharge test was 1.6V to 0.2V, and the scan rate was 5mV / s.
[0072] The power density of the assembled flexible zinc-air battery is Figure 8 As shown in Figure 1, the peak power density of the solid-state flexible zinc-air battery assembled directly as a self-supporting integrated air cathode using the catalyst of Example 1 is as high as 136 mW / cm 2 , superior to commercial Pt / C catalyst.
[0073] Considering the actual application scenarios of flexible batteries, stress bending tests were carried out on the assembled flexible zinc-air batteries, such as Fig. 9 As shown in Figure 2, the battery exhibits a stable charge and discharge curve at different bending angles, demonstrating its potential to provide energy for future portable and wearable electronic devices.
[0074] In summary, the present invention provides a self-supporting carbon nanofiber-supported high-spin Fe single-atom catalyst and its preparation method and application as a cathode of a flexible zinc-air battery, which specifically relates to the technical field of preparation of electrode materials for flexible zinc-air batteries. The preparation method provided by the present invention uses electrospinning technology combined with high-temperature pyrolysis strategy to prepare a self-supporting carbon nanofiber-supported high-spin Fe single-atom catalyst (Fe-N4 / N GC -C), carbon nanofibers ensure that the active sites of Fe single atoms are fully exposed, and their high conductivity accelerates charge transfer. GC -C catalyst has more unpaired electrons, which can penetrate the antibonding π* orbital of O2 and effectively activate the reactants, so that the self-supporting catalyst of the present invention achieves low load and high catalytic performance. In addition, the present invention is directly used as an integrated air electrode to assemble the cathode of a flexible zinc-air battery, which not only simplifies the assembly steps and reduces the cost of electrode preparation, but also achieves excellent performance under bending conditions and successfully powers wearable electronic watches, showing broad development prospects in the field of flexible and wearable electronic devices.
[0075] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a self-supporting carbon nanofiber-supported high-spin iron single-atom catalyst, characterized in that: The Fe-ZIF-8 nanofibers obtained by electrospinning technology were sintered at high temperature to obtain self-supporting carbon nanofibers loaded with high-spin iron single-atom catalysts.
2. The method according to claim 1, characterized in that: The following steps are included: Step 1: preparing Fe-ZIF-8 powder: mixing a zinc source solution and an iron source solution to obtain a Fe-Z1F-8 precursor solution; the iron source is iron nitrate, and the zinc source is zinc nitrate; Step 2: preparing Fe-ZIF-8 seed crystals: heating and stirring the Fe-ZIF-8 precursor solution obtained in step 1, centrifuging, washing, and drying to obtain Fe-ZIF-8 seed crystals; Step 3: Preparation of Fe-N4 / N GC -C catalyst precursor: adding polyacrylonitrile and the Fe-ZIF-8 seed crystals into N,N-dimethylformamide solvent, stirring, and obtaining a polymer solution containing Fe; using electrospinning technology to spin the polymer solution to obtain Fe-N4 / N GC -C catalyst precursor; Step 4: Preparation of self-supporting carbon nanofibers loaded with high spin iron single atom catalyst: Fe-N4 / N GC The -C catalyst precursor is first pre-oxidized, and the pre-oxidized sample is sintered at high temperature in a nitrogen atmosphere to obtain a self-supporting carbon nanofiber-loaded high-spin iron single atom catalyst.
3. The preparation method according to claim 2, characterized in that: In step 1, the mass ratio of ferric nitrate to zinc nitrate is 1:25-30.
4. The preparation method according to claim 2 or 3, characterized in that: In step 2, the heating and stirring temperature is 55-65° C. for 10-14 h; the temperature of the vacuum oven is set to 80° C. for 12 h.
5. The preparation method according to claim 2 or 3, characterized in that: In step 2, the drying temperature is 60 to 80° C. and the drying time is 10 to 24 hours.
6. The preparation method according to claim 2 or 3, characterized in that: In step 3, the mass ratio of polyacrylonitrile, Fe-ZIF-8 seed crystals and N,N-dimethylformamide solvent is 4-5:1:7-8.
7. The preparation method according to claim 2 or 3, characterized in that: In step 3, the conditions for electrospinning are: the amount of spinning solution is 5 to 8 mL, the applied voltage is 20 to 22 kV, the propulsion speed is 1 to 1.2 mL / h, the receiving distance is 10 to 15 cm, and the air humidity is 40 to 50%.
8. The preparation method according to claim 2 or 3, characterized in that: In step 4, the pre-oxidation temperature is 280-300°C, the heating rate is 4-5°C / min, the sintering time is 2-3h, and the temperature is naturally lowered.
9. The preparation method according to claim 2 or 3, characterized in that: In step 4, the high-temperature sintering temperature is 1000°C, the heating rate is 5°C / min, the sintering time is 2h, and the temperature is naturally lowered.
10. Application of the catalyst prepared by the method for preparing the self-supporting carbon nanofiber-supported high-spin iron single-atom catalyst according to claim 1 in a flexible zinc-air battery, characterized in that: The self-supporting carbon nanofibers loaded with high-spin iron single-atom catalysts are directly used as the cathode of a flexible zinc-air battery.
Citation Information
Patent Citations
Composite electrocatalyst, preparation method and application thereof
CN113652706A
Carbon nanofiber loaded metal monatomic catalyst as well as preparation method and application thereof
CN114744370A
Monatomic catalyst-loaded porous carbon fiber material as well as preparation method and application thereof
CN115939408A
Monatomic iron-loaded graded porous hollow carbon fiber catalyst as well as preparation method and application thereof
CN118867279A
Cited By
Iron-nickel diatomic fiber catalyst with precise and adjustable local structure as well as preparation method and application of iron-nickel diatomic fiber catalyst
CN121192183A